How does land fragmentation affect off-farm labor supply: panel data evidence from China - Lili Jia; Martin Petrick (Agricultural Economics, 2014)
This article provides a deeper theoretical understanding of the linkages between land fragmentation and off-farm labor supply in China, and investigates this relationship empirically in a more direct way than does the existing literature. Drawing upon a rural household panel data set collected in Zhejiang, Hubei, and Yunnan Provinces from 1995 to 2002, we estimate the effects in two steps. First, we estimate the effect of land fragmentation on labor productivity. Second, we estimate the effect of land fragmentation on off-farm labor supply. The production function results show that land fragmentation indeed leads to lower agricultural labor productivity, implying that land consolidation will make on-farm work more attractive and thus decrease off-farm labor supply. However, the effect of land consolidation on off-farm labor supply is not significant. One likely explanation for this result may be the potentially imperfect labor markets.
Keywords: J22; Q15; Q24; R23; 330; Land fragmentation; Off-farm; Labor supply; China